Assessing diapocynin's different effects on osteosarcoma and breast cancer cells: An in vitro study - Santos, Fernanda Cesar dos; Mochetti, Matheus Menão; Tokuhara, Cíntia Kazuko; Pessoa, Adriano de Souza; Inacio, Kelly Karina; Sanches, Mariana Liessa Rovis; Ximenes, Valdecir Farias [UNESP]; Oliveira, Rodrigo Cardoso de (Elsevier, 2025)
Osteosarcoma is the most common primary bone cancer, accounting for approximately 5 % of new cancer cases globally. In contrast, breast cancer remains the most prevalent malignancy and a leading cause of cancer-related mortality among women. Given the limitations of current therapies, novel treatment strategies are urgently needed. This study evaluates the effects of diapocynin, a derivative of apocynin, on osteosarcoma (UMR-106) and breast cancer (MDA-MB-231) cell lines. Our results demonstrate a dose-dependent cytotoxicity of diapocynin in both cell types, with UMR-106 cells showing higher sensitivity than MDA-MB-231 cells. Notably, treatment with diapocynin induced significant morphological changes in both cell lines, and both IC25 and IC50 concentrations effectively inhibited cell migration, particularly in osteosarcoma cells. However, no significant changes were detected in matrix metalloproteinases −2 and −9 activity following treatment, suggesting that diapocynin may exert its effects through alternative pathways. These results highlight diapocynin as a promising candidate for cancer therapy, warranting further investigation into its mechanisms of action and potential clinical applications.
Keywords: Breast cancer cell; Diapocynin; Osteosarcoma